Muscarinic receptors participation in angiogenic response induced by macrophages from mammary adenocarcinoma-bearing mice - de la Torre, Eulalia (2006)
Introduction The role of macrophages in tumor progression has generated contradictory evidence. We had previously demonstrated the ability of peritoneal macrophages from LMM3 murine mammary adenocarcinoma-bearing mice (TMps) to increase the angiogenicity of LMM3 tumor cells, mainly through polyamine synthesis. Here we investigate the ability of the parasympathetic nervous system to modulate angiogenesis induced by TMps through the activation of the muscarinic acetylcholine receptor (mAchR). Methods Peritoneal macrophages from female BALB/c mice bearing a 7-day LMM3 tumor were inoculated intradermally (3 × 105 cells per site) into syngeneic mice. Before inoculation, TMps were stimulated with the muscarinic agonist carbachol in the absence or presence of different muscarinic antagonists or enzyme inhibitors. Angiogenesis was evaluated by counting vessels per square millimeter of skin. The expression of mAchR, arginase and cyclo-oxygenase (COX) isoforms was analyzed by Western blotting. Arginase and COX activities were evaluated by urea and prostaglandin E2 (PGE2) production, respectively. Results TMps, which stimulate neovascularization, express functional mAchR, because carbachol-treated TMps potently increased new blood vessels formation. This response was completely blocked by preincubating TMps with pirenzepine and 4-diphenylacetoxy-N-methylpiperidine (4-DAMP), M1 and M3 receptor antagonists, and partly by the M2 receptor antagonist methoctramine. M1 receptor activation by carbachol in TMps triggers neovascularization through arginase products because N ω-hydroxy-L-arginine reversed the agonist action. Preincubation of TMps with methoctramine partly prevented carbachol-stimulated urea formation. In addition, COX-derived liberation of PGE2 is responsible for the promotion of TMps angiogenic activity by M3 receptor. We also detected a higher expression of vascular endothelial growth factor (VEGF) in TMps than in macrophages from normal mice. Carbachol significantly increased VEGF expression in TMps, and this effect was totally reversed by methoctramine and pirenzepine. Arginase and COX inhibitors partly decreased VEGF derived from TMps. Conclusion TMps themselves induce a potent angiogenic response that is augmented by carbachol action. mAchR activation triggers arginine metabolism, PGE2 synthesis and VEGF production, promoting neovascularization.